The first collected “Shakespeare Apocrypha” - Kirwan, Peter (Johns Hopkins University Press, 2011)
The anonymous plays Mucedorus, The Merry Devil of Edmonton, and Fair Em derive their spurious attribution to Shakespeare from a volume entitled "Shakespeare Vol. 1" that once belonged to David Garrick. Despite its significance, this volume has not been studied for over two hundred years. This note corrects two longstanding errors concerning the volume's provenance and constitution, dating it to the 1630s and revealing that the volume contained eight plays, rather than the three usually assumed. Drawing out the implications of this information, Kirwan argues that the volume thus represents the first attempt to compile a volume of Shakespearean dubitanda. Situating the volume between the Pavier project and the Chetwynd Third Folio, he suggests that it implies an earlier and more sustained period of instability in the formation of the Shakespeare canon than is usually believed, and that even before the closure of the theatres, perceptions of the constitution of the Shakespeare canon were already unfixed.